Being a DJ in a time of zero social huddling: Tales from a locked-down India. Issue Volume 21:Number 1(2021)Special Issue:Part 1 (28th August 2021) - Sarkar, Pradip
Abstract : The COVID-19 pandemic has caused widespread disruptions in music industries globally, resulting in rapid cancellations of music festivals, concerts and club nights, and closure of international borders. The consequences of this pandemic have been especially dire for musicians, DJs and event promoters whose livelihoods and financial viability were tied largely to live performances. Within the independent music scenes in India, artists and event organizers rushed to social media and livestreaming platforms in their attempts to salvage brand visibility and explore monetization opportunities as drastic impositions of nationwide lockdowns came into effect. In a densely populated developing country rife with anxieties over exponential rates of COVID-19 infections, independent musicians in India have sought creative approaches to maintain visibility through digital platforms. Drawing on methods influenced by online ethnography, this article presents a discussion of how four professional Indian DJs explore and interrogate the affordances of various social media and livestreaming platforms in their efforts to remain artistically visible in the absence of state-initiated financial support and socially huddled dance-floors. The article offers insights into the triumphs, and trials and tribulations, experienced by independent musicians as they explore the material affordances of digital platforms at this critical moment in history.